Antimicrobial Resistance of Escherichia coli From Aquaculture Farms and Their Environment in Zhanjiang, China - Liao, Cui-Yi; Balasubramanian, Balamuralikrishnan; Peng, Jin-Ju; Tao, Song-Ruo; Liu, Wen-Chao; Ma, Yi (Frontiers in Veterinary Science, 2021)
The antimicrobial resistance (AMR) has become a major concern worldwide. To evaluate the AMR of E. coli in aquaculture farms of Zhanjiang, China, a total of 90 samples from water, soil and sediment of three aquaculture farms (farm I, II, III) in Zhanjiang were collected, and 90 strains of E. coli were isolated for drug resistance analysis and AMR genes detection. The results indicated that the isolated 90 strains of E. coli have high resistance rates to penicillin, amoxicillin, ampicillin, tetracycline, compound sulfamethoxazole, sulfisoxazole, chloramphenicol, florfenicol and rifampin (≥70%), among these antimicrobial drugs, the resistance rate to rifampicin is as high as 100%. Among the isolated 90 strains of E. coli, all of them were resistant to more than two kinds of antimicrobial drugs, the number of strains resistant to 9 kinds of drugs was largest (19 strains) and the most resistant strain showed resistance to 16 kinds of antibacterial drugs. Regarding the AMR genes, among the three aquaculture farms, the most resistance genes were detected in farm II (28 species). The detection rate of blaTEM, blaCIT, blaNDM, floR, OptrA, cmlA, aphA1, Sul2, oqxA, and qnrS in 90 isolates of E. coli was high (≥50%). The detection rate of carbapenem resistance genes such as blaKPC、blaIMP and cfr was relative lower (≤30%), and the detection rate of mcr2 was the lowest (0). At least 4 AMR genes were detected for each strain, and 15 AMR genes were detected at most. Among them, the number of strains carried 10 AMR genes was the largest (15 strains). Finally, correlation analysis found that the AMR genes, including blaTEM, blaCIT, floR, OptrA, cmlA, aac(3)-Ⅱ, Sul2, ereA, ermB, oqxB, qnrA, mcr1 and mcr2, had a high correlation rate with the drug resistance (≥50%). To summarize, the 90 strains of E. coli isolated from water, surrounding soil and sediment samples showed resistance to multi antimicrobial drugs and carried various antimicrobial resistance genes. Thus, it is essential to strengthen the rational use of antimicrobial drugs, especially the amide alcohol drugs, and control the AMR in the aquaculture industry of Zhanjiang, China.